A Feasibility Study on the Waste-to-Biogas SOFC-Based Multi-Generation with Energy Storage System for Building Applications in China. (June 2019) - Zhang, S; Wang, Q; Hu, L; Shi, W; Qu, M
Abstract: The Waste-to-Energy Multi-generation system provides a feasible distributed waste recycling and energy saving solution for green buildings. However, the fluctuations in electricity demands and dynamic built environment obstruct its marketization. This study optimizes the existing waste-biogas-SOFC multi-generation configuration with energy storage systems. The research employs the operation data from an international airport in Southern China as a case study. The study compares the proposed system and that of previous SOFC-based systems in terms of economic and environmental benefits. The results show that the demand and supply of energy is balanced and higher energy efficiency and a significant reduction in the Greenhouse Gas (GHG) emission is achieved. The system presents a solid performance in payback and lifecycle cost (LCC) analysis and also satisfactory resistance to financial risks. Finally, this study draws the conclusion that the energy storage system could be utilized to optimize the existing SOFC multi-generation system.